Morphological Behavior of the Prefix 'In-' and Its Assimilated Forms in English Negation - Riandana, Martinus Hergirico; Bram, Barli (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
This study aimed to find the underlying form of the prefixes in-, im-, il-, ir- and morphological processes occurring in the complex words containing those prefixes. The researchers focus on the negation, meaning only words with a prefix that changes the initial meaning of the root word into a negative meaning are qualified. Descriptive analysis was employed. Seventy qualified words from the Oxford English Dictionary were chosen to be analysed. The researchers formulated two research questions: (1) What is the underlying form of the prefixes in-, im-, il-, and ir-? and (2) What morphological processes occurred in the complex words containing prefixes in-, im-, il-, and ir-? The findings showed that the prefix in- is the underlying form of those prefixes seen from the lenses of morphology and phonology. Further, affixation is a morphological process that occurs in complex words containing those prefixes. This study contributes to shaping a better understanding of the prefix in- and its assimilated forms for English educators and language learners. Implications are discussed.